Interaction of batrachotoxin with the local anesthetic receptor site in transmembrane segment IVS6 of the voltage-gated sodium channel - Linford, Nancy J. (The National Academy of Sciences, 1998)
The voltage-gated sodium channel is the site of action of more than six classes of neurotoxins and drugs that alter its function by interaction with distinct, allosterically coupled receptor sites. Batrachotoxin (BTX) is a steroidal alkaloid that binds to neurotoxin receptor site 2 and causes persistent activation. BTX binding is inhibited allosterically by local anesthetics. We have investigated the interaction of BTX with amino acid residues I1760, F1764, and Y1771, which form part of local anesthetic receptor site in transmembrane segment IVS6 of type IIA sodium channels. Alanine substitution for F1764 (mutant F1764A) reduces tritiated BTX-A-20-α-benzoate binding affinity, causing a 60-fold increase in K(d). Alanine substitution for I1760, which is adjacent to F1764 in the predicted IVS6 transmembrane alpha helix, causes only a 4-fold increase in K(d). In contrast, mutant Y1771A shows no change in BTX binding affinity. For wild-type and mutant Y1771A, BTX shifted the voltage for half-maximal activation ≈40 mV in the hyperpolarizing direction and increased the percentage of noninactivating sodium current to ≈60%. In contrast, these BTX effects were eliminated completely for the F1764A mutant and were reduced substantially for mutant I1760A. Our data suggest that the BTX receptor site shares overlapping but nonidentical molecular determinants with the local anesthetic receptor site in transmembrane segment IVS6 as well as having unique molecular determinants in transmembrane segment IS6, as demonstrated in previous work. Evidently, BTX conforms to a domain–interface allosteric model of ligand binding and action, as previously proposed for calcium agonist and antagonist drugs acting on l-type calcium channels.